Differential effects of oleate on vascular endothelial and liver sinusoidal endothelial cells reveal its toxic features in vitro (2023)
ABSTRACT: Several fatty acids, in particular saturated fatty acids like palmitic acid, cause lipotoxicity in the context of non-alcoholic fatty liver disease . Unsaturated fatty acids (e.g. oleic acid) protect against lipotoxicity in hepatocytes. However, the effect of oleic acid on other liver cell types, in particular liver sinusoidal endothelial cells (LSECs), is unknown. Human umbilical vein endothelial cells (HUVECs) are often used as a substitute for LSECs, however, because of the unique phenotype of LSECs, HUVECs cannot represent the same biological features as LSECs. In this study, we investigate the effects of oleate and palmitate (the sodium salts of oleic acid and palmitic acid) on primary rat LSECs in comparison to their effects on HUVECs. Oleate induces necrotic cell death in LSECs, but not in HUVECs. Necrotic cell death of LSECs can be prevented by supplementation of 2-stearoylglycerol, which promotes cellular triglyceride (TG) synthesis. Repressing TG synthesis, by knocking down DGAT1 renders HUVECs sensitive to oleate-induced necrotic death. Mechanistically, oleate causes a sharp drop of intracellular ATP level and impairs mitochondrial respiration in LSECs. The combination of oleate and palmitate reverses the toxic effect of oleate in both LSECs and HUVECs. These results indicate that oleate is toxic and its toxicity can be attenuated by stimulating TG synthesis. The toxicity of oleate is characterized by mitochondrial dysfunction and necrotic cell death. Moreover, HUVECs are not suitable as a substitute model for LSECs.